Microbial decomposition of porcine tissue in organic compost at different temperatures. Issue Volume 1(2019)Issue A (8th March 2019) - Franicevic, Branka; Fletcher, Jonathan; Wilson, Andrew; Janaway, Rob
Abstract : Laboratory experiments were conducted to determine the effect of temperature (20 °C and 30 °C) on the rate of tissue decomposition in organic compost for a period of 28 days. Porcine tissue was used as a substitute for human body parts in burial microenvironment. Measurements of the decay include porcine tissue mass loss, soil pH, the metabolic activity of soil microbes, viable count and Gram stain of associated microflora. Incubation temperature had a significant impact on the post-mortem decay rates and stages at 30 °C in comparison to the samples incubated at 20 °C. Bacterial enumeration demonstrated microbial burden to be higher at higher temperatures, suggesting accelerated decomposition. Gram staining identified mostly Gram-negative bacteria, decomposers that might have originated from the organic meat as opposed to soil bacteria. There was a significant difference in soil pH levels during harvest times and at the end of the experiments in both microenvironments. It is an indication that measured pH of the depository may reveal whether the body parts were recently buried. A fluorescein diacetate (FDA) method that measured metabolic activity in compost demonstrated the highest release of fluorescein during harvests at 30 °C. A non-parametric Friedman test of differences among repeated measures rendered significant results (α=0.00) showing differences in microbial activity according to the temperature level. The results suggest that depositional microenvironment would be significantly modified by the decaying organic matter with the rise of temperature. This way, the temperature would make an impact on the decay of buried remains.